(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
Ulcerative colitis is a chronic inflammatory condition in which patients show altered bowel habit such as diarrhoea, constipation, rectal bleeding, tenesmus, passage of mucous and crampy abdominal pain etc. These symptoms may be relapsing and remitting episodes of inflammation limited to the muscles layer of colon. Allopathic medicine definitely made the life comfortable for human beings with various research and advancement in treatment modalities but in certain disease like ankylosing spondylitis, psoriatic arthritis, rheumatoid arthritis, inflammatory bowel disease and many more diseases it also searches a search engine and probably Ayurveda play this role in several ways. In Ayurveda Raktaja Arsh, Raktatisara, Raktaja Pravahika, Grahani shows symptoms having resemblance with Ulcerative colitis. Ayurveda described various treatment modalities for the management of Ulcerative colitis such as Anuvasan Basti, Piccha Basti, Samshamanyogas, proper nutritional supplements, herbal therapy, Yoga and meditation etc. In present study, A diagnosed case of ulcerative colitis, age 61yrs male from Dhanbad, Jharkhand came to OPD of Kayachikitsa, Government Ayurvedic College and Hospital, Patna. He complained of pain in abdomen, bleeding per rectum, excessive thirst, pain in joints of lower limb bilaterally. He was given Anuvasan Basti and Piccha Basti along with some drugs and his complaints not only relieved delayed remission as well. The goals of the treatment are to improve quality of life, minimize the risk of colon cancer and achieve steroids free remission of the disease ulcerative colitis.